Clinical complete response after nivolumab administered as a third-line treatment for unresectable advanced gastric cancer with peritoneal dissemination: A case report. (July 2021) - Komo, Toshiaki; Suzuki, Takahisa; Tazawa, Hirofumi; Sada, Haruki; Morimoto, Hiroshi; Shimada, Norimitsu; Hadano, Naoto; Onoe, Takashi; Sudo, Takeshi; Shimizu, Yosuke; Tashiro, Hirotaka
Abstract: Introduction and importance: Nivolumab, which is a fully human IgG4 PD-1 immune checkpoint inhibitor antibody, has been recommended as a third-line treatment based on the results of the ATTRACTION-2 study involving patients with unresectable advanced gastric cancer. Case presentation: A 69 year-old woman was referred to our department with a diagnosis of gastric cancer based on an upper gastrointestinal endoscopy during a medical examination. The endoscopy, along with various tests, helped establish a diagnosis of unresectable advanced gastric cancer (cT4aN3aM1P1c, cStage IV) with peritoneal dissemination. The first and second-line chemotherapy administered was S-1 plus oxaliplatin followed by ramucirumab and nab-paclitaxel, respectively. In this case, the disease was evaluated as progressive disease due to increased peritoneal dissemination. Nivolumab was administered as the third-line treatment. The patient developed interstitial pneumonia after nine courses of nivolumab, for which chemotherapy was discontinued and prednisolone treatment was initiated. The patient had a complete response to treatment endoscopically, 9 months after the last administration of nivolumab. After that, there was no recurrence of the cancer, despite there being no treatment for 5 months. Clinical discussion: It was suggested that the therapeutic effect of nivolumab could be maintained for a long period after discontinuation of its administration. In addition, a correlation has been reported between the treatment efficacy and immune-related adverse events associated with nivolumab. Conclusions: The synergistic effect of the sustained effect of nivolumab and later-line treatment may contribute to the prolongation of survival after discontinuation of nivolumab in patients who are refractory or intolerant to treatment. Highlights: Nivolumab is recommended as third-line treatment in patients with unresectable advanced gastric cancer. Nivolumab is expected to have a long tail effect. The synergistic effect of nivolumab and the later-line treatment may contribute to the prolongation of survival.